Analisis Common Size Statement Pada PT. Asuransi Jiwasraya (Persero) Cabang Manado Kota - Billy Monok; Johny Montolalu; Henny S. Taroreh (Universitas Sam Ratulangi, 2018)
This study aims to determine and assess the company's financial performance is assessed by common size analysis techniques, comparison and profitability ratios through financial statements. Analysis of financial performance of insurance companies is important to review, in order to assess whether the insurer is always able and in a position to always pay every sentence proposed by the policyholder. This study was conducted to determine the development of financial performance, health level and financial ratings of insurance companies PT. Asuransi jiwasraya (Persero) from 2014 to 2015 common size analysis method used is the analysis of insurance-specific financial ratios of RBC, liquidity, mandatory reserve deposit ratio, total investment ratio per technical reserve, total investment ratio per technical reserve and debt of kalim, the ratio of fixed assets to equity, the ratio of net investment income per investment average, the ratio of expenses (claims + business + commissions) per net premium income, and the ratio of income before tax per average equity to standard benchmark set by the finance ministry; trend; and common size statement. This study aims to benjwab two formulation of the problem, based on the results of analysis and discussion based on data analysis of financial statements balance sheet using the method of common size in the company 2014 and 2015 that the company's financial performance in sufficient data data balance sheet that has increased there 13 while the contents of the report profit loss based on the analysis of common size that has been done, it can be seen that there are 26 posts that have increasedÂ Keywords: analysis, common size, financial statement